The modelled costs of adaptation - Watkiss, Paul; Bruin, Kelly de; Dasgupta, Shouro; Ebi, Kristie; Hinkel, Jochen; Hunt, Alistair; Lincke, Daniel; Rozenberg, Julie; Sayer, Pieter; Shariq, Ammara; Sulser, Timothy B.; Tiggeloven, Timothy; et al. (United Nations Environment Programme, 2023)
Key messages ▶ The Adaptation Finance Gap (AFG) Update 2023 has undertaken an updated modelling assessment of the cost of adaptation for developing countries. This analysis has used a suite of global sector assessment models, complemented by new analysis in additional sectors. ▶ The update analysis estimates the plausible central costs of adaptation at approximately US$240 billion per year this decade (up to 2030), with a range of US$130–415 billion per year. The central estimate is equivalent to 0.56 per cent of the gross domestic product (GDP) (2021) for all developing countries (or approximately US$33 per capita/per year). ▶ The highest adaptation costs are for river flood protection, infrastructure and coastal protection, and for the regions of East Asia and the Pacific and Latin America and the Caribbean. ▶ The highest absolute costs are for the upper- and lower-middle-income countries. However, when expressed as a percentage of GDP, adaptation costs are much higher for low-income countries (3.5 per cent) than for lower-middle-income (0.7 per cent) and upper-middle-income (0.5 per cent) countries. ▶ The costs for lower-income and lower-middle-income countries are estimated at US$76 billion per year this decade: the costs for small island developing States (SIDS) alone are estimated at US$4.7 billion per year (0.7 per cent of their GDP) and for least developed countries (LDCs) at US$25 billion per year (2 per cent of their GDP). ▶ The modelled costs of adaptation are estimated to increase significantly by 2050, especially for high-warming scenarios. ▶ These updated costs show a significant increase compared to previous similar studies. This not only reflects the more negative impacts of climate change reported in the literature (for the sectors previously modelled), but also a wider range of risks and sectors.